Edukasi Mitos dan Fakta Sayur dan Buah Bagi Remaja di SMA N 9 Tanjung Jabung Timur - Arnati Wulansari; Ayu Widia Sari; Arsa Ninda (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Myth is one of the causes of nutritional problems in adolescents. There is a lot of knowledge in the form of myths that have been passed down from generation to generation by teenagers with scientifically uncertain truths, including adolescense girls at SMA N 9 Tanjung Jabung Timur. This is one of the causes of the low consumption of vegetables and fruit on the grounds of not avoiding vegetables and fruit due to myths. This community service activity was carried out at SMA N 9, Tanjung Jabung Timur Regency. The implementation of this activity will be from February 2021 to July 2021. The target of this activity is SMA N 9 Tanjung Jabung Timur students. The method used in the implementation of this activity is the lecture and discussion method. The results obtained in this activity are the target of understanding the material about myths and facts about vegetables and fruits. It is suggested to the school to be able to work together with the puskesmas and the local Health Office to provide education regarding the benefits of vegetables and fruit.